Prone position ventilation and nursing management for a patient with respiratory distress syndrome caused by COVID-19 (1例新型冠状病毒感染致呼吸窘迫综合征患者俯卧位通气法的应用及护理) - LI Shuyue (李淑悦); LI Ying (李影); REN Yaxing (任亚星); WANG Jing (王晶); CAO Wenjie (曹文杰); LI Han (李涵); YANG Yuwei (杨雨薇); LI Shuo (李硕); HAN Jianping (韩建萍); FENG Yajing (冯亚静) (Journal of International Translational Medicine Limited, 2023)
This paper summarized the effect of prone position ventilation and nursing management for a patient with respiratory distress syndrome caused by COVID-19. The compressive nursing assessment, airway management and tube fixation were conducted before using prone position ventilation for therapy. After implementation of prone position ventilation for therapy, efforts had been made to enhance the vital signs monitoring, tube maintenance, airway management, nutrition support and prevention of pressure injuries. (本文总结1例新型冠状病毒感染致呼吸窘迫综合征患者俯卧位通气法的应用效果及护理体会。操作前系统评估患者和完善物品准备, 保持气道通畅和妥善固定管道; 操作后密切监测患者生命体征, 加强导管维护、呼吸道护理和营养支持, 积极预防压力性损伤。)